Editorial - Martina Grunow; Hilmar Schneider; Gert G. Wagner; Joachim Wagner (International Journal for Re-Views in Empirical Economics (IREE), 2018)
Lack of reproducibility is seriously undermining the credibility of science as a whole. By extrapolating the findings of isolated checks, one may expect a substantial fraction of published articles in scientific journals to contain findings that simply do not hold. But we do not know which articles are affected - they usually remain uncovered.
Keywords: 330